Topological integrated circuits for 5G and 6G - Kumar, Abhishek (2022)
On-chip Floquet photonic topological insulators, which are based on switched-capacitor circulators, could be used to create hybrid electronic–photonic topological integrated circuits for emerging communication technologies.